2014
DOI: 10.4103/2225-4110.131373
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Two Herbal Mouthwashes on Gingival Health of School Children

Abstract: This study aimed at determining the effect of indigenously prepared neem and mango chewing stick mouthwashes on plaque and gingival indices. A sample of 105 children aged 12-15 years was randomized into three groups, namely neem, mango, and chlorhexidine mouthwash groups. All the children were examined at baseline and gingival and plaque indices were recorded. Baseline scores for plaque and gingivitis were fair and moderate, respectively, in all the three groups and there existed no statistically significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 27 publications
1
28
0
1
Order By: Relevance
“…Another study was done on children and it was concluded that neem and mango chewing sticks mouthwashes mouthwashes were effective antiplaque & antigingivitis agents with neem & CHX possessing equivalent antiplaque efficacy while CHX having superior antigingivitis properties when used for twice daily for 21 days. [56]Similar results with neem extract mouthrinse were also seen in other study [57].…”
Section: Fig 2 Depiction Of Role Of Neem (Azadirachta Indica) In Desupporting
confidence: 77%
“…Another study was done on children and it was concluded that neem and mango chewing sticks mouthwashes mouthwashes were effective antiplaque & antigingivitis agents with neem & CHX possessing equivalent antiplaque efficacy while CHX having superior antigingivitis properties when used for twice daily for 21 days. [56]Similar results with neem extract mouthrinse were also seen in other study [57].…”
Section: Fig 2 Depiction Of Role Of Neem (Azadirachta Indica) In Desupporting
confidence: 77%
“…For thousands of years, various herbal and natural products have been used for chemotherapeutic purposes in the field of medicine and dentistry, with the advantage of few side effects and cost鈥恊ffectiveness 12 . Aloe vera (AV) is one such medicinal, a perennial succulent plant belonging to the Xanthorrhoeaceae family with anti鈥恑nflammatory, 13 antioxidant, 14 antibacterial, 15 antiviral, 16 antifungal, 17 and immune鈥恇oosting properties 18 .…”
mentioning
confidence: 99%
“…On the other hand, the presence of ethanol in commercial mouthwash seems to be problematic due to different reported side effects (28). A review of studies has shown that Jaftex has shown antibacterial activity against common oral microorganisms and periodontal indexes in vitro and in vivo conditions (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41).The antibacterial property of this mouthwash is largely attributed to the extract of Jaft (30).According to a review of the past studies, thyme and Saturej bachtiarica have some antibacterial effects. The antibacterial effects of these two products are attributed to the compounds of their elements.…”
Section: Discussionmentioning
confidence: 99%
“…Like the fruit, Jaftalso has health benefits (19)The antibacterial activities of different parts of oak have been studied in several studies (20)(21)(22).Medicinal herbs are particularly valuable in providing community health in both disease treatment and prevention (23).The use of natural products in dentistry has been justified by their popular use, low cost and appropriate antimicrobial, and antiinflammatory activities (24).The mouth is a perfect environment for colonization and growth of a wide range of microorganisms, especially bacteria (25). Dental plaque is a complex of microbial community found on the surface of teeth, embedded in a matrix of bacteria and salivary origin (26).The bacteria are responsible for 70-80 percent of the plaques (27).Mouthwashes are oral solutions or liquids used 4 to rinse the mouth in order to remove bacteria (28).Chlorhexidine (CHX) is a golden chemical antiplaque, however, it may cause side effects due to the long usage (29).Herbal mouthwashes are more proper than CHX because they contain organic compounds, which aremore fitted with body physiology, and they have lower toxicity; therefore, they are recommended for people who cannot use chemical mouthwashes (27).Jaftex is a new herbal mouthwash that consistsof Jaft aquatic extract as a base, aquatic extract of Zataria multiflora(Thyme), and Saturej bachtiarica;this herbal mouthwashis prepared scientifically in the Pharmaceutical Plant Growth Center of Ahvaz Jundishapur University of Medical Sciences (30).The antibacterial effects of Jaftex mouthwash have been studied in the few studies (27,28,30,31).…”
Section: Introductionmentioning
confidence: 99%